Organ removal of maize increases peanut canopy photosynthetic capacity, dry matter accumulation, and yield in maize/peanut intercropping - Liu, Zhu; Nan, Zhenwu; Lin, Songming; Meng, Weiwei; Xie, Liyong; Yu, Haiqiu; Zhang, Zheng; Wan, Shubo (Frontiers in Plant Science, 2023)
In maize/peanut intercropping systems, shade from maize is a major factor in peanut yield reduction. Reasonable redundant organ removal of maize plants could alleviate this problem and improve intercropped peanut yields. We studied the influences of organ removal of maize on peanut canopy photosynthetic capacity, dry matter accumulation and yield in maize/peanut intercropping systems in 2021 and 2022. Five organ-removal treatments were performed on maize plants to ameliorate the light environments in the peanut canopy. Treatments consisted of removal of the tassel only (T1), the tassel with top two leaves (T2), the tassel with top four leaves (T3), the tassel with top six leaves (T4), the leaves below the second leaf below the ear (T5), with no removal as control (T0). The results showed that organ-removal treatment (T4) significantly improved the photosynthetically active radiation (PAR, 49.5%) of intercropped peanut canopy. It improved dry matter accumulation by increasing the canopy photosynthetic capacity (canopy apparent photosynthetic rate (CAP), leaf area index (LAI), and specific leaf area (SLA)), ultimately contributing to peanut yield by increasing pod number per plant. Also, the above results were verified by structural equation modeling. The yield of intercropped peanut reached the highest value at T4. At the level of intercropping systems, the land equivalent ratio (LER) peaked at T2 (1.56, averaged over the two years), suggesting that peanut and maize can coexist more harmoniously under T2 treatment. The T2 treatment increased peanut yield by an average of 7.1% over two years and increased maize yield by 4.7% compared to the T0 treatment. The present study suggests that this may be an effective cultivation measure to mitigate intercropping shade stress in terms of adaptive changes in intercropped peanut under maize organ removal conditions, providing a theoretical basis for intercropped peanut yield increase.